Investigation of low switching frequency control of a three phase cascaded H-bridge multilevel inverter - Hasan, M.; Abu-Siada, Ahmed; Islam, M. (2017)
© 2016 IEEE. This paper presents analysis of a three phase hybrid multilevel inverter (MLI) by applying low frequency stair case control strategy. The proposed MLI contains three cascaded stages, auxiliary stage-1, auxiliary stage-2, and main stage. The main stage contains three half-bridge cells which are connected in parallel with a common DC power supply. Each of the stages in the auxiliary stages consists of three H-bridge where the H-bridge cells contain isolated DC power supplies. The proposed hybrid MLI is tested for symmetric and asymmetric configurations of input voltage sources of the main and auxiliary stages. A scaled down prototype of the proposed hybrid three-phase hybrid MLI is developed to verify the control concept and the real time performance of the inverter.